Consumer-brand relationship: Foundation and state-of-the-art - Loureiro, S.M.C. (Customer-centric marketing strategies: Tools for building organizational performance, 2013)
The relationship between a brand and consumers is known to produce positive outcomes for both partners. Consumers develop relationships with diverse brands regarding brands as partners. Brands are humanized in the minds of consumers and therefore provide symbolic meanings and social and cultural value, which is beyond the utilitarian benefits. Following this paradigm, the purpose of this chapter is to show an overview of the research from customer relationship management to consumer-brand relationship and propose a theoretical model of consumer-brand relationship process. In this vein, the chapter begins with the conceptualization of customer relationship management. Then, the foundation, an overview of main theories, and the seminal models of consumer-brand relationship are shown. Finally, a model of consumer-brand relationship process is proposed and insights for further research are provided.